Development of Statistical Literacy-Based e-Modules for Pre-service Teachers Learning Statistics - Idris, Khairiani; Ramli, Mahdalena; Harun, Jamilah (Jurnal Pendidikan MIPA, 2024)
The concepts of statistics could be hard to understand by students without grasping the problem context. Using an easy-to-understand context or context that is close to the students in statistics learning materials could help students’ understanding of the statistical concept. This research and development study was conducted to develop an e-module based on statistical literacy for pre-service teachers learning statistics. The topics of e-module developed consisted of topics related to the introduction to statistics and data presentation while using some Islamic contexts and values that are close to the participants. The research was conducted in two stages: the developmental stage and the experimental stage. The developmental stage included problem analysis and literature studies, development of the initial e-module, validation and revision of the e-module. The experimental stage included testing the effectiveness of the e-module for 164 pre-service teachers from 7 study programs of IAIN Lhokseumawe, Aceh. The quantitative data from this experimental phase was analyzed using ANCOVA by controlling prior knowledge in statistics and digital literacy skills to evaluate the influence of the e-module on participants’ performance in statistics. The qualitative data of the interview transcripts was analyzed using content analysis. The statistical analysis results showed no significant difference in statistical performance between students using the e-module and students using conventional learning texts. However, from the interviews, we found that, in general, students acknowledged that the e-module used was interesting and that it facilitated their understanding of statistical concepts. However, they encountered obstacles when accessing the e-module due to the weak and unstable internet connection. Suggestions were provided for future research direction to ensure the effectiveness of using the developed e-module.         Keywords: e-module, islamic contexts, statistical literacy, statistical cognitions, pre-service teachers. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1080-1098